Japan Evaluation Society: Pilot Test of an Accreditation Scheme for Evaluation Training - Masafumi Nagao (The Evaluation Center at Western Michigan University, 2005)
The Japan Evaluation Society (JES) has conducted a pilot test of an accreditation scheme for short-term evaluation training programs. The program chosen for this test was a 4-day school evaluation training course organized by a public teacher training center in cooperation with Hiroshima University.